Cultural Differences in Parenting Practices - MURRAY, AISLING (ESRI, 2011)
There is an increasing acceptance across the disciplines of psychology, sociology and health that an individual?s development does not take place in a social vacuum (see for example Bronfenbrenner?s bio-ecological model, e.g. Bronfenbrenner & Morris, 2006). The development of infants, in particular, is influenced by their parents: relying on them for food, shelter, protection, health care and fostering development. Hence we might expect that those individuals and organisations which influence parents (grandparents, friends, the media) will also have an indirect, but important, influence on infants
PUBLISHED
Dublin
ESRI Research Bulletin 2010/04/04
Keywords: Sociology; Education